(untitled) (Journal of Applied Learning and Teaching, 2024)
This article contributes to the ongoing discussion about the impacts of utilizing emerging technologies – especially AI learning – in higher education. After reviewing the pros and cons of using ChatGPT in the classroom as they are typically considered, I raise a deeper, less frequently addressed concern: the pervasive persistence of Eurocentric biases in the academy and the danger that AI-empowered software will reinforce them further. To this end, I present the findings of a simple experiment I conducted, directing ChatGPT to produce and refine a syllabus for an undergraduate course on modern political philosophy, together with an essay responding to one of the questions set in the syllabus. The results clearly demonstrate the grave potential for such supposedly ‘time-saving’ technological shortcuts to re-inscribe Eurocentric thinking and unconscious biases, thus seriously complicating the vital, already challenging task of decolonizing the academy.